Dakwah dalam Perspektif Organisasi Produksi: (Studi Konten Video Keislaman Youtube Bayt Al-Quran) - Ibnu Abbas, Muhammad; Mauli Darajat, Deden (IAIN Madura, 2022)
This study answers the question of how to preach social media Islamic video content on YouTube Bayt Al-Al-Quran in the perspective of a production organization. Regarding what was prepared in the pre-production process and what was done during the production process as well as the strategies used in publishing Islamic video content. Bayt Al-Quran is a mosque and Islamic boarding school under the auspices of the Center for Al-Quran Studies. One of the da'wah activities carried out is presenting videos of Islamic studies through Youtube. Youtube, which is already familiar to the audience, is widely used for the development of da'wah. The resulting video content is created through a series of production processes until video studies can be followed through the Youtube platform. The method used in this research is descriptive analytical method using three theories related to production organization, namely Pre Production, Production and Post Production from Gill Branston and Roy Stafford to the production of Islamic content in Bayt Al-Quran. Bayt Al-Quran as a da'wah organization presents positively charged content on the Youtube platform. The results showed that there were obstacles in the production process but the manufacture of Bayt Al Quran was able to overcome them. The finished video content is then distributed through the Youtube platform. The uploaded video content allows the audience to watch it anytime and anywhere.